PENGARUH KECERDASAN INTELEKTUAL DAN KECERDASAN SOSIAL TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN GOWA - Fajar, Restu Ichwal (Universitas Teuku Umar, 2024)
The purpose of this study was to determine the effect of intellectual intelligence and social intelligence on employee performance at the Gowa Regency Social Service. The type of research used in this study is quantitative using the SPSS 26 program data analysis method. The sample in this study was 49 people who were employees of the Gowa Regency Social Service. The data analysis used was descriptive data analysis, research instrument analysis, classical assumption analysis, multiple linear regression analysis and hypothesis testing.The results of this study indicate that based on the results of data analysis and t-test results, it was obtained that the intellectual intelligence variable has a positive but insignificant effect on employee performance at the Gowa Regency Social Service, so H1 is rejected and H0 is accepted. This is evidenced by a significance value of 0.943> 0.05. Conversely, the social intelligence variable has a significant effect on employee performance. This is evidenced by a significance value of 0.047 <0.05, which means that H1 is accepted and H0 is rejected. Keywords : intellectual intelligence, social intelligence and employee performance